PERSEPSI PEDAGANG KAKI LIMA TERHADAP KREDIT USAHA RAKYAT - Didit Darmawan; Siti Nur Halizah; Ella Anastasya Sinambela; Rahayu Mardikaningsih (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2022)
One sector that plays an important role in a country's economy is micro, small and medium enterprises (MSMEs). The utilization of micro, small and medium enterprises has had a positive impact on the growth and prosperity of a country. Therefore, the government is developing interest in micro, small and medium enterprises to advance the country's economy. The purpose of this research is to find out the perceptions of street vendors on Kredit Usaha Rakyat (KUR) and to find out the relationship between efforts to apply for KUR and interest in developing a business. The object of this study is focused on street vendors. There were 126 respondents who were involved by accidental sampling. Furthermore, the data will be analyzed descriptively. The correlation between applying for KUR and interest in developing a business is positive and very strong.